199 Electronic Clinical Decision Support for Children with Mild Traumatic Brain Injuries and Intracranial Injuries: A Sociotechnical Analysis. (1st April 2022) - Greenberg, Jacob K.; Otun, Ayodamola; Carpenter, Christopher; Brownson, Ross; Kuppermann, Nathan; Limbrick, David D.; Yen, Po-Yin; Foraker, Randi
Abstract : INTRODUCTION: The management of children with mild traumatic brain injuries (mTBI) and intracranial injuries is not evidence-based and may place some children at risk of harm. Evidence-based electronic clinical decision support (CDS) may improve patient safety and decrease resource use. METHODS: We conducted semi-structured qualitative focus group interviews to identify sociotechnical influences on CDS implementation. Physicians from neurosurgery, emergency medicine, critical care, and pediatric general surgery were included, along with information technology specialists. Participants were recruited from nine hospitals in the United States. Focus group transcripts were coded and analyzed using thematic analysis. The final themes were cross-referenced with previously defined sociotechnical dimensions. RESULTS: We included 28 physicians and four information technology specialists in seven focus groups. Ten participants had administrative leadership positions, and the largest group (34%) was from neurosurgery. Through inductive thematic analysis, we identified five primary themes: 1) clinical impact; 2) stakeholders and users; 3) tool content; 4) clinical practice integration; and 5) post-implementation evaluation measures. Participants generally supported using CDS to determine an appropriate level-of-care for these children, and also noted potential secondary uses (e.g., informing family discussions). However, some also identified potential harm that could result from misuse (e.g., conflict across specialties). Feedback from the interviews helped refine the tool content, highlight potential implementation barriers, and identify appropriate measures to evaluate after implementation. CONCLUSION: We identified key factors impacting the implementation of electronic CDS for children with mTBI and intracranial injuries, providing a strong foundation for prospective implementation efforts.